2017
DOI: 10.5455/medarh.2017.71.330-333
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preoperative Anxiety in Patients on Hemodynamic Changes and a Dose of Anesthetic During Induction of Anesthesia

Abstract: Objectives:Each surgical patient is preoperatively, intraoperatively and postoperatively exposed to stress. The aim of this study was to determine the existence of preoperative anxiety, and to determine its impact on hemodynamic parameters (blood pressure, heart rate) in patients and dose of anesthetics during induction of anesthesia.Methods:A prospective clinical study conducted at the Department of Anesthesiology and Reanimation and Surgery Clinic of University Clinical Center Tuzla (UCC) in the period May 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 8 publications
0
21
0
2
Order By: Relevance
“…Surgery and anesthesia bring significant degrees of stress to the patient, and the use of anesthetic drugs and hemodynamic fluctuations and other operating room (OR) events can affect the patient's memory status and, therefore, lead to patients' dissatisfaction. [ 15 ] This has led to extensive researches in patients undergoing nonneurologic surgeries. [ 16 ] Memory and learning are among the most complex and important behavioral processes, and as the spectrum of anesthetic worldwide use is expanding, knowledge about the effects of these drugs on the memory process is of particular importance.…”
Section: Introductionmentioning
confidence: 99%
“…Surgery and anesthesia bring significant degrees of stress to the patient, and the use of anesthetic drugs and hemodynamic fluctuations and other operating room (OR) events can affect the patient's memory status and, therefore, lead to patients' dissatisfaction. [ 15 ] This has led to extensive researches in patients undergoing nonneurologic surgeries. [ 16 ] Memory and learning are among the most complex and important behavioral processes, and as the spectrum of anesthetic worldwide use is expanding, knowledge about the effects of these drugs on the memory process is of particular importance.…”
Section: Introductionmentioning
confidence: 99%
“…Patient-reported anxiety levels in our study were comparable with other studies such as Oldman et al (2004) who measured anxiety on the morning of surgery (mean STAI ≈33). However, Ahmetovic-Djug et al (2017) investigating preoperative anxiety found a higher mean STAI (53). Only 15% of our study population achieved high anxiety scores on the STAI; this is lower than reported anxiety in other perioperative studies where the incidence of anxiety ranges from 60 to 92% ( Perks et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Anas Alatas 1* , Irfan Meison Hardi 1 , Eddy Harijanto 1 Pemasangan Peripheral Intravenous Catheter (PIVC) merupakan salah satu prosedur invasif yang paling banyak dilakukan di rumah sakit dengan lebih dari 70% pasien rawat inap membutuhkan pemasangan infus selama masa perawatan. 1 Sebanyak 40% pasien dilakukan pemasangan PIVC sebagai akses pengambilan sampel darah, dan sebanyak 25% pasien dipasangan PIVC sebagai akses untuk terapi cairan di unit gawat darurat (UGD). Pemasangan PIVC pada pasien penting untuk berbagai intervensi terapeutik, seperti terapi cairan, penggantian elektrolit, terapi antibiotik, nutrisi parenteral, pemberian zat kontras, dan prosedur anestesia.…”
Section: Comparison Of Effectiveness Of Vibration Anesthesia Device (...unclassified